Minding the Happiness Gap: Political Institutions and Perceived Quality of Life in Transition - Milena Nikolova (Institute for the Study of Labor (IZA), 2015)
Along with political and economic changes, the fall of the socialist regimes in Central and Eastern Europe and the former Soviet Union brought about fundamental institutional reforms. Several studies have examined the causes of the increasing unhappiness which accompanied the transition process, including deteriorating public goods, rising inequality, income volatility, stagnating labor market conditions, and changing norms. Yet, few papers have sought explanations for the life satisfaction differentials between transition and non-transition economies. In this paper, I specifically examine the life satisfaction gap between post-socialist and advanced countries and the role of political institutions in explaining this gap. My results imply that both macroeconomic factors and the rule of law explain the overall life satisfaction differential between the advanced and transition societies. The rule of law had an additional role of reducing the happiness gap in the 1990s and may have even reversed it in the post-crisis years. As institutions and macroeconomic conditions continue to improve, post-socialist countries may complete their transformation processes and achieve quality of life levels comparable with those in the West.
Keywords: D02; E02; I31; P20; 330; subjective well-being; institutions; transition economies